Innovative development as a factor in improving the competitiveness of the enterprises of mining - metallurgical complex of Kazakhstan. (Journal of Economic Research & Business Administration, 2015)
The article deals with the priority directions of innovative development of Kazakhstan's mining - metallurgical enterprises.